Reframing adolescent research - Hendry, Leo B.; Kloep, Marion, 1955- (Routledge, 2019)
How can we ensure that adolescent research is really assisting the optimal developmental transitions of young people, now and in the near future? Reframing Adolescent Research suggests that what is needed is a 'paradigm-shift', a movement towards implementing more systemic, innovative and inter-disciplinary approaches to youth research, which are more suited to resolving the real issues that young people face in the twenty-first century. Contributions from world-class academics examine theoretical concerns and methodological challenges to substantive areas in the field, considering possible limitations and weaknesses in current approaches. They argue for the need for 'unorthodox,' systemic inter-disciplinary research which looks beyond the social sciences to consider innovations and novel approaches to the study of adolescence and development across the lifespan. New theories, methods and interventions are presented that are essential to advancing the project of understanding adolescents and how they develop on a global stage.This ground-breaking volume will encourage debate and dialogue on the future of youth research. It is valuable reading for advanced students and researchers in adolescent development and developmental psychology.
Keywords: Adolescent psychology -- Research -- Methodology.; Adolescence -- Research -- Methodology.; Adolescence -- Recherche -- Méthodologie.; FAMILY & RELATIONSHIPS / Life Stages / General; PSYCHOLOGY / Developmental / General; PSYCHOLOGY / Developmental / Lifespan Development; PSYCHOLOGY / General